Description Of The Level Of Patient Satisfaction With The Appearance And Taste Of Regular Food Served At Mataram City Hospital - AASP Chandradewi; Aulya Riska Febriani; Luh Suranadi; I Nyoman Adiyasa; Reni Sofiyatin (Jurnal Gizi Prima (Prime Nutrition Journal), 2022)
Background. The level of patient satisfaction is an indicator in assessing the quality of food service in hospitals. Annisa et al. (2021), in their research, stated that 92.6% of respondents were dissatisfied with the taste of food, and 53.7% of respondents were dissatisfied with the appearance of food. Taking into account the various problems above, the purpose of this study was to describe the level of patient satisfaction with the appearance and taste of ordinary food served at Mataram City Hospital. Research Methods. Knowing the description of the level of patient satisfaction with the appearance and taste of ordinary food served at the Mataram City Hospital. This research is descriptive. The study was conducted from February to March 2022 for 15 days. The population is all inpatients in class III who get regular food at lunchtime. Samples were 23 patients who were determined as samples by purposive sampling. Data analysis was performed univariately. Data about the appearance and taste of the food were obtained by interview using a questionnaire. Research Result. The level of satisfaction with the food appearance, including the color category, is quite satisfied at 95.7%, the form category is satisfied at 87%, and the presentation in the class is quite happy at 78.3%. Meanwhile, the food taste aspect includes aroma in the somewhat satisfying category 43.5%, taste in the satisfied category 34.8%, texture in the 82.6% comfortable type, and temperature in the 56.5% happy category.  Conclusion. Overall, the level of patient satisfaction in the category of satisfied with the appearance of food is 87%, and the level of patient satisfaction in the type of quite happy with the taste of food is 65%.